Factors Affecting Employee Motivation at the Samarinda Center for Drug and Food Control - Jubaidi, Jubaidi; Yudha, Dody Tri (International Journal Labs, 2024)
Motivation of subordinates is very important because with motivation they are expected to work hard and enthusiastically so that they can achieve high work productivity. Increasing work motivation can be done by providing incentives, social security, creating a good organizational culture and having superior policies that are easy for employees to accept. BPOM Samarinda Center really needs employees who have high work motivation so that they will have high productivity in improving services to the community in the field of drug and food control. The purpose of this research is to analyze various variables that are used as factors that influence employee work motivation at the Samarinda Balai BPOM. The data analyzed came from questionnaires distributed to 96 employees. Data collection uses saturated sampling (population) techniques. Data analysis used multiple linear regression analysis using the SPSS 22 program. The results showed that simultaneously all independent variables had a significant effect on employee work motivation, while partially only the incentive variable had no significant effect on employee work motivation, whereas social security, organizational culture and policy superiors partially have a significant effect on employee work motivation.